Association between Anticholinergic Drug Impact on Nutritional Status in Older Adults at Outpatient Department of Phramongkutklao Hospital - Jatujinda, Sutthida; Gesakomol, Kulachede; Matesareyapong , Korawee; Srisuwan, Patsri (Journal of The Royal Thai Army Nurses, 2024)
The purposes of this cross-sectional study aimed to investigate the relationship between anticholinergic drug use and malnutrition in older adults. Data were collected using the Mini Nutritional Assessment Short Form (MNA-SF) questionnaire to screen for malnutrition and the Drug Burden Index (DBI) to assess anticholinergic drug use in patients aged over 60 years who visited the outpatient department of Phramongkutklao Hospital. Data was analyzed using descriptive statistics and logistic regression, The results showed that anticholinergic medication use is associated with an increased risk of malnutrition in elderly. Compared to the control group (MNA-SF ≥ 12), the adjusted odds ratio (AOR) for developing risk of malnutrition (MNA-SF = 11-8) and malnutrition (MNA-SF = 7-0) was 1.78 times (95%CI 1.22 - 2.60, p = .003) and 1.99 times (95%CI 1.24 - 3.18, p = .004), respectively. This research offers insights for nurses and other healthcare providers to enhance the care of older adults. By implementing strategies to minimize medication side effects and promote safe medication practices.